Efeito dos substituintes p-fenil nas propriedades luminescentes de novos complexos de európio(III) e gadolínio(III) com hidrazidas - Brandão, Samira Gomes (2019)
New lanthanides (Eu3+ and Gd3+) complexes with hydrazides were successfully synthesized and the effect of the p-phenyl substituent on the Eu3+ luminescent properties was evaluated. Crystals of Gd-amino was obtained and its structure was elucidated by single-crystal X-ray diffraction, revealing Gd3+ centered in a distorted tricapped trigonal-prismatic molecular geometry. IR spectroscopy and the elucidated structure confirmed hydrazides acting as bidentate ligands binding to Ln3+ ions through the oxygen of carbonyl group and the nitrogen of terminal amine, forming a five-membered ring. The CHN indicated the molecular formulas [Gd(amino)4(H2O)](NO3)3·(C2H5OH) and [Eu(toluic)3(H2O)3](NO3)3, the Gd3+ complex had its structure also confirmed by X-ray diffraction in single crystal. Lower T1 state energies were observed for ligands p-substituted with higher electron donating capacity groups and higher oscillator strength, such as p-OH and p-NH2. In contrast, higher lifetimes and quantum efficiencies were obtained for Eu-complexes with p-H and p-CH3 substituents, which are not deactivator groups and weaker oscillators.